Augmented reality application for architects and interior designers: interno a cost effective solution - Nasir, Sidra; Zahid, Mohammad Noman; Khan, Talha Ahmed; Kadir, Kushsairy Abdul; Khan, Sheroz (IEEE, 2019)
Now a days with excessive work load and busy life, many professional face problems that results in the loss of their clients or the certain overheads that spoil the process of satisfying the client. The proposed software will be used by interior designers or architects. This proposed research most likely acts as an effective tool which can decrease the gap between industrial company and customer in addition to other applicable business communities. It will help in visualizing architect plans and interior designs. A virtual model of real environment can be designed before its physical implementation, it will allow interior designers to implement their idea in the given workspace virtually and then view it in real environment, it will also allow architects to view their 3D visualizations on their 2D drawings. Application is based on my findings of user’s expectations of an augmented reality interior design service, a service which is a combination of various functionality of social media, augmented reality (AR) and 3-D modeling that encloses the concept of home design. This study distinctively bridges all users of relevant businesses to the user-intensive design of an augmented reality. The paper provides you with the inner depth on how the augmented reality can be implemented to facilitate the architects and interior designers as well it discusses the algorithm used to achieve the functionalities. The proposed application exhibits two types of Augmented reality, Marker less and marker based. The novelty of the project is that it does not require any sort of expensive gadgets. It can easily be used via smartphones and tablets. It is also operable on any operating system. This is a cost-effective solution that primarily reduces the overheads that interior designer and architects confronts on daily basis. The software exhibits all the features that might be required by interior designers and architects respectively.